2013
DOI: 10.1108/09513541311297568
|View full text |Cite
|
Sign up to set email alerts
|

Assessing student satisfaction in transnational higher education

Abstract: Given that there exists in the literature relatively little research into student experiences in transnational higher education, this study seeks to identify the determinants of student satisfaction at international branch campuses in the United Arab Emirates (UAE). This quantitative study involved 247 undergraduate and postgraduate students at branch campuses in the UAE who completed a questionnaire using either hard copies or an online version. It was found that levels of student satisfaction at UAE branch c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
160
2
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(180 citation statements)
references
References 38 publications
10
160
2
8
Order By: Relevance
“…Competition between universities to attract quality students has intensified as institutions try to grow domestically and internationally [3], [27]. This competitive environment has resulted in students having a greater variety of institutions to select from.…”
Section: Student Satisfactionmentioning
confidence: 99%
“…Competition between universities to attract quality students has intensified as institutions try to grow domestically and internationally [3], [27]. This competitive environment has resulted in students having a greater variety of institutions to select from.…”
Section: Student Satisfactionmentioning
confidence: 99%
“…quality of learning outcomes, quality of advising, quality of administrative and technical support) and process (i.e. the efficiency of administrative and technical operations as well as the school climate) of the learning environment (Maddox & Nicholson, 2014;Wilkins & Balakrishnan, 2013).…”
Section: Outline Of the Resultsmentioning
confidence: 99%
“…M. Hill, 1995;Y. Hill et al, 2003;Mai, 2005;Negricea et al, 2014;Ravindran and Kalpana, 2012;Roman, 2014;Sakthivel et al, 2005;Wang and Tseng, 2011;Wilkins et al, 2013; were also found to significantly affect student satisfaction with quality of higher education services. Similarly, many earlier studies (de Kleijn et al, 2012;Harman, 2003;Khosravi et al, 2013;Munteanu et al, 2010;Sutton and Sankar, 2011;Zhao et al, 2007) underlined the importance of academic advising services on student satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…However, education is no longer limited to high school and college experiences since more and more students undertake graduate courses (Wang and Tseng, 2011). Indeed, a number of studies (Arambewela and Hall, 2008;Barnes and Randall, 2012;de Kleijn et al, 2012;Harman, 2003;Sutton and Sankar, 2011;Uysal, 2015;Wilkins and Stephens Balakrishnan, 2013;Zhao et al, 2007) have successfully concentrated on postgraduate students' expectations and satisfaction. Nevertheless, further research is periodically needed to better understand postgraduate students' level of satisfaction and which indicators contribute to their satisfaction levels for improving the quality of higher education services.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation